AbaKu: An Abacus Teaching and Learning Courseware / Nur Safawate Mohd Shaari - Mohd Shaari, Nur Safawate (2018)
The learning session using abacus has been emphasized in mathematics subject for students in primary school. With the advancement of technology during this era, the way to deliver education to students in school will be more exciting. Moreover, if the method of the delivery is involving games, it also can improve the student’s understanding based on what they have learned. According to the current abacus learning sessions, most of the schools use only textbooks as their guides. Therefore, the students are required a lot of efforts to understand on what their teachers have taught. The purpose of developing this courseware is to provide an additional learning tool for students to learn how to use the abacus for calculation. Furthermore, teachers and parents can use it as a teaching tool. The proposed courseware helps to attract the students to learn by implementing multimedia and gamification elements in this courseware. In this project, this courseware was developed by using ADDIE Model which consists of five stages, starting with the analysis, design, development, implementation and the last stage is the evaluation. This courseware was evaluated by the three experts to examine the functionality and usability of AbaKu Courseware. In fact, the evaluation also involved 30 respondents by distributing the questionnaires about courseware. Based on the results collected, most respondents are satisfied with the AbaKu Courseware interface with the highest mean which is 4.63 (SD = 0.49). In conclusion, AbaKu Courseware can be an additional tool and learning aids at school and home for students, teachers and parents. However, the courseware can be improved by adding more interactive elements in the future development.